Main-d'oeuvre requise pour la culture du mais sur des jacheres et sur des sols precedemment voues a Stylosanthes - zone subhumide du Nigeria - Tarawali, G.; Mohamed-Saleem, M.A.; Kaufmann, Ralph R. von (1987)
Examines the returns to labour from cropping fallowed land and land that has been used for stylosanthes fodder banks in the subhumid zone of Nigeria.